A Rasmussen encephalitis, autoimmune encephalitis, and mitochondrial disease mimicker: expanding the DNM1L‐associated intractable epilepsy and encephalopathy phenotype. Issue 1 (27th March 2019) - Nolan, Danielle A.; Chen, Baibing; Michon, Anne Marie; Salatka, Emily; Arndt, Daniel
ABSTRACT: Dynamin‐1‐like protein ( DNM1L ) gene variants have been linked to childhood refractory epilepsy, developmental delay, encephalopathy, microcephaly, and progressive diffuse cerebral atrophy. However, only a few cases have been reported in the literature and there is still a limited amount of information about the symptomatology and pathophysiology associated with pathogenic variants of DNM1L . We report a 10‐year‐old girl with a one‐year history of mild learning disorder and absence seizures who presented with new‐onset focal status epilepticus which progressed to severe encephalopathy and asymmetric hemispheric cerebral atrophy. Differential diagnosis included mitochondrial disease, Rasmussen's encephalitis, and autoimmune encephalitis. Disease progressed from one hemisphere to the other despite anti‐seizure medications, hemispherectomy, vagus nerve stimulator, ketogenic diet, and immunomodulators. Continued cerebral atrophy and refractory seizures evolved until death four years after initial presentation. Post‐mortem whole‐exome sequencing revealed a pathogenic DNM1L variant. This paper presents a novel case of adolescent‐onset DNM1L ‐related intractable epilepsy and encephalopathy.